2020
DOI: 10.1186/s12886-020-01400-5
|View full text |Cite
|
Sign up to set email alerts
|

Ripasudil alleviated the inflammation of RPE cells by targeting the miR-136-5p/ROCK/NLRP3 pathway

Abstract: Background Inflammation of RPE cells led to different kinds of eye diseases and affected the normal function of the retina. Furthermore, higher levels of ROCK1 and ROCK2 induced injury of endothelial cells and many inflammatory diseases of the eyes. Ripasudil, which was used for the treatment of glaucoma, was one kind of the inhibitor of ROCK1 and ROCK2, but whether ripasudil could relieve the LPS-induced inflammation and damage of RPE cells was not clear. Methods We used LPS to stimulate ARPE-19 cells, the R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…MiR-136-5p was shown to be involved in retinopathy, evidenced by its aberrant downregulation of miR-136-5p in LPS-treated retinal pigment epithelium cells (27). MiR-136-5p repression enhanced the production of inflammatory factors in LPS-treated retinal pigment epithelium cells (27). Besides, miR-136-5p was also involved in AKI, evidenced by its poor expression in HK2 cells treated with hypoxia/reoxygenation (28).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-136-5p was shown to be involved in retinopathy, evidenced by its aberrant downregulation of miR-136-5p in LPS-treated retinal pigment epithelium cells (27). MiR-136-5p repression enhanced the production of inflammatory factors in LPS-treated retinal pigment epithelium cells (27). Besides, miR-136-5p was also involved in AKI, evidenced by its poor expression in HK2 cells treated with hypoxia/reoxygenation (28).…”
Section: Discussionmentioning
confidence: 99%
“…At 36 dpi, cfa-miR-136 was downregulated 1.91 times. The upregulation of cfa-miR-136 alleviates inflammatory injury [ 52 ]. IL17f , one of the potential target genes of cfa-miR-136, was successfully assigned to 15 significantly enriched GO terms at 36 dpi, such as regulation of inflammatory response, regulation of response to stimulus, and regulation of response to wounding.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In addition, miR-136-5p also could suppress chondrocyte degeneration 26 and was related to the inflammation of retinal pigment epithelial. 27 Sand et al analyzed the differentially expressed miRNA in CSCC and normal skin tissue, and found that miR-136 was a significantly downregulated miRNA in CSCC. 28 In this study, our data suggested that miR-136-5p could be promoted by GSPs in vitro and in vivo, and it also could reverse the enhancing effect of hsa_circ_0070934 on the progression of GSPs-treated CSCC cells.…”
Section: Discussionmentioning
confidence: 99%